Pengaruh Manajemen Aset Terhadap Kinerja Keuangan Pada PT . Astra International Tbk Periode 2012-2021 - Vevbi Verra; Endah Kurniawati; Ririn Wahyu Arida (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
This researcher aims to determine the effect of asset management on financial performance at PT. Astra International Tbk. The variables of this study are total asset turnover (X1), fixed asset turnover (X2), working capital turnover (X3), and operating profit (Y). This study uses a quantitative method in the form of financial reports from 2012 to 2021, the sample used is 40 and the source of data from this research is the quarterly financial reports of PT. Astra International Tbk. The data collection technique in this research is to use a documentation study. Data analysis techniques in this study used the classical assumption test, hypothesis testing, multiple linear regression analysis and the coefficient of determination test. Data processing in this study used the software program SPSS (Statistics Package for the Social Sciences) 25.0 for windows. By using a level of 5% or 0.05 with the results (1) partially the total activation turnover has a significant effect on operational profit with a significance value of 0.000 <0.05 which means H0 is rejected and Ha is accepted. (2) partial activation turnover still has a significant effect on operating profit with a significance value of 0.004 <0.05, which means H0 is rejected and Ha is accepted. (3) partially working capital turnover affects operational profit with a significance value of 0.000 <0.05, which means that H0 is rejected and Ha is accepted. (4) simultaneously total asset turnover, fixed asset turnover, and working capital turnover have a significant effect on operating profit with a significance value of 0.000 <0.05 which means H0 is rejected and Ha is accepted.